PENGARUH INOVASI PRODUK, KUALITAS PELAYANAN, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOPI KENANGAN - Putri, Aini Adrianti; Mugiono, Mugiono (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Every coffee shop competes to present its flagship coffee product by offering a selection of coffee beans both from Indonesia and abroad. This research aims to identify the direct and indirect effects of product innovation, service quality, and promotion on people’s decision to purchase Kopi Kenangan products. This research is considered as explanatory research as it tries to explain the causal relationship between variables through hypothesis testing. Using purposive sampling technique, 114 people within the age range of 18-30 years who live in Malang and have purchased the products of Kopi Kenangan at least once were selected as the respondents. The data was harvested through questionnaires, library research, and web browsing. The data was assessed using validity test, reliability test, and classical assumption test, while the multiple linear regression analysis and the hypothesis testing were performed in SPSS 22. This study finds that product innovation, service quality, and promotion positively and significantly influence purchase decision.